Kobiety – sprawczynie przestępstw : wybrane aspekty - Brzezińska, Joanna; Habzda-Siwek, Ewa (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The book presents reflections on women - perpetrators of crime from several complementary perspectives. The theoretical part presents diverse criminological theories that may be helpful in explaining the phenomenon of women's crime, with particular emphasis on the so-called integrated concept. The next part of the paper presents the most important criminal law and criminological issues concerning several categories of crimes committed by women. The analysis covers, inter alia, crimes against life and health (homicide, infanticide), crimes against property, traffic offences, as well as some offences related to domestic violence. The third chapter is devoted to the characteristics of the structure and dynamics of women’s crime in Poland based on data from court statistics made available by the Ministry of Justice. The last part presents selected criminal cases of homicides committed by women. The issues presented in the book made it possible to outline the various determinants of the phenomenon of women's crime. Their explanation was intended to provide a comprehensive view of the phenomenon under study and its accompanying mechanisms.
Keywords: female crime; criminological theories; homicide; infanticide; domestic violence; statistical anlysis